Effect of culture media on production of polyunsaturated fatty acids by pavlova lutheri - Carvalho, Ana P. (2011)
Use of microscopic algae as sources of polyunsaturated fatty acids for incorporation as feed additive in aquaculture has received increasing interest owing to beneficial effects upon growth rates of zooplankton. However, the biochemical composition of marine algae is a function of the composition of the culture medium. Pavlova lutheri is particularly interesting because it is able to modulate the fatty acid profile of its lipidic fraction when cultured with various nutrient media. Three enriched seawater media (i.e. GPM, f/2 and MN) and one synthetic medium (i.e. ASW), covering considerable quantitative and qualitative ranges of nutrients, were tested in order to determine the medium compositions that stimulate production of such polyunsaturated fatty acids as EPA and DHA, and the biochemical compositions of the algae grown in each were monitored accordingly. Relationships between the mineral components of the medium and the resulting biomass yield, as well as the biochemical profile and the polyunsaturated fatty acid productivity, are tentatively presented in attempts to shed further light on the effects of the processing environment upon microalgae. Statistical analyses of the experimental results have indicated that GPM provides the best compromise in terms of cell yield (12.1 × 106 cell mL−1) and polyunsaturated fatty acid productivities (0.502 mg l−1 d−1 and 0.228 mg l−1 d−1 in EPA and DHA, respectively). In addition, GPM is a simple medium, mainly composed of seawater, nitrogen and phosphorus, thus having a low production cost and being easy to prepare in industrial settings, so it is suitable for general use in aquaculture of marine species.